Studies on Bhartṛhari and the Pratyabhijñā: The Case of svasaṃvedana - Marco Ferrante (Religions, 2017)
The article addresses a critical problem in the history of South Asian philosophy, namely the nature of the ‘knowledge of knowledge’ (svasaṃvedana). In particular, it investigates how the Śaiva tantric school of the Pratyabhijñā (10th–11th c. CE) used the notion as an argument against the Buddhists’ ideas on the nature of the self. The paper then considers the possibility that the source of the Śaivas’ discussion was the work of the philosopher/grammarian Bhartṛhari (5th c. CE).